Comparative analysis of the nutritional composition, digestibility, metabolomics profiles and growth influence of cow, goat and sheep milk powder diets in rat models - Yang, Chun; Pan, Jiancun; Pang, Shaojie; Hu, Shuang; Liu, Miao; Zhang, Xinyan; Song, Liping; Ren, Xiangnan; Wang, Zhongli (Frontiers in Nutrition, 2024)
The study aims to explore the nutritional composition, growth performance, digestibility, and serum metabolic differences of milk powders from cow, goat, and sheep using LC-MS/MS-based metabolomics in rat models. Sixty male rats were fed milk powder samples, and their feces and urine were then analyzed for fat and protein content. Among all the samples, the sheep milk powder showed highest protein and fat content level, while cow and goat milk powders separately demonstrated higher lactose and carbohydrate levels. Each milk powder had a unique mineral profile, with sheep milk powder containing the highest calcium content. All groups exhibited consistent growth in body weight and high rates of protein and fat digestibility.Metabolomics analysis revealed distinct metabolic profiles, with goat milk powder linked to steroid hormone biosynthesis and sheep milk powder associated with hormone regulation and bile acid pathways. The study indicates that understanding the sources of milk is crucial for effective dietary planning.